Photodegradation of basic red 51 in hair dye greywater by zinc oxide nanoparticles using central composite design - Yashni, G.; Al-Gheethi, Adel; Radin Mohamed, Radin Maya Saphira; Arifin, Siti Nor Hidayah; Mohd Salleh, Siti Nor Aishah (Springer, 2020)
The current work aimed to optimize the photocatalysis of Basic Red (BR51) in hair dye greywater (HDG) using zinc oxide nanoparticles (ZnO NPs) by response surface methodology (RSM). The independent factors included ZnO NPs dose (10–200 mg), pH (3–9) and BR51 (1–10 ppm). The photocatalysis efficiency of the ZnO NPs was determined based on the decolorization of BR51 and chemical oxygen demand (COD) reduction. The photocatalysis mechanism was investigated based on the ZnO NPs analyses by field emission scanning electron microscopy/energy dispersive X-ray analysis (FESEM/EDX), Fourier transform infrared (FTIR) spectroscopy, Thermogravimetric analysis and differential scanning calorimetry (TGA/ DSC), atomic force microscope (AFM), and Raman spectroscopy. The optimal operating factors for the photocatalysis of BR51 were recorded at 131.56 mg of ZnO NPs, pH 3, and 7.47 ppm of BR51, where 72.18 vs. 70.93% of BR51 removal and 82.71 vs. 83.56% of COD removal were the observed and predicted results recorded with an R2 coefficient of 0.92. The independent variables exhibited a significant (p < 0.05) interaction with 95% of confidence level. FESEM and AFM analysis showed that the grain sizes of ZnO NPs were uniform before photodegradation but aggregated afterwards. FTIR analysis revealed the main functional groups of ZnO NPs that contributed to the removal process were –C–O, =C–H, C=C, –C–O–C, and OH. TGA revealed a mass loss and exothermic reaction due to desorption of the chemisorbed water. Raman spectroscopy indicated the crystal structure of ZnO for ZnO NPs (before) and the decrease in the crystalline quality for ZnO NPs (after). These findings indicated that ZnO NPs have a high potential for the photocatalysis of BR51 in HDG.